Leaching of rapidly quenched Al65Cu20Fe15 quasicrystalline ribbons - Mishra S.S.; Yadav T.P.; Mukhopadhyay N.K.; Srivastava O.N. (My University, 2025)
In the present work, Al65Cu20Fe15 alloy has been synthesized by melting of pure elements (e.g., Al (99.96%), Cu (99.99%) and Fe (99.98%)), using a radiofrequency induction melting furnace. The as-prepared alloy was subjected to rapid solidification by melt spinning technique at ∼ 3500 rpm speed on a copper disk of diameter 14 cm. As a result of the melt spinning, nearly 2 mm wide, 30−40 μm thick and 4–5 cm long ribbons were formed. The structural and microstructural characterizations were carried out by X-ray diffraction and transmission electron microscopy techniques. We have performed leaching operation using 10 mol NaOH aqueous solution on the surface using a pipette. Leaching was performed for various durations ranging from 30 min to 8 h. After leaching, the reflectivity reduces and the surface looks reddish brown. The microstructure of the 8 h leached sample shows a breakdown of the quasicrystalline phase but with the evolution of other metallic phases. Copper (Cu) particles are found to be present on the surface of quasicrystal after 4 h of leaching and relatively more iron (Fe) evolves during further leaching of 8 h. This low-cost method to prepare a distribution of nano-Cu/Fe metal particles encourages their uses in catalytic reactions, indicating the possibility of use of quasicrystals as the industrial catalysts. © Indian Academy of Sciences.